A Theory of ISIS Political Violence and the Transformation of the Global Order - Mohamedou, Mohammad-Mahmoud Ould (Pluto Press, 2017)
The Islamic State of Iraq and Syria has been the subject of intense scrutiny in the West. Considered by many to be the most dangerous terrorist organisation in the world, it has become shrouded in numerous myths and narratives, many emanating from the US, which often fail to grasp its true nature.Against these narratives, Mohammad-Mahmoud Ould Mohamedou presents a bold new theory of ISIS. By tracing its genealogy and documenting its evolution in Iraq and Syria, he argues that ISIS has transcended Osama Bin Laden's original project of Al Qaeda, mutating into an unprecedented hybrid form that distils postcolonial violence, postmodernity and the emerging post-globalisation international order.This book analyses ISIS from a social sciences perspective and unpacks its dynamics by looking beyond superficial questions such as its terrorist nature and religious rhetoric. It transforms our understanding of ISIS and its profound impact on the very nature of contemporary political violence.